Philosophy of Dionysius the Areopagite : an introduction to the structure and the content of the treatise On the Divine Names - Schäfer, Christian, 1967-. (Philosophia Antiqua, 2006)
This book proposes a reading of Dionysius the Areopagite's longest and most important treatise 'On the Divine Names' from a philosophical point of view, rather than from a theological point of view which dominates the secondary literature. More in particular, it proposes an interpretation of the puzzling structure of the treatise which takes its starting point from earlier interpretations of medieval and modern scholars. The new reading of Dionysius' main text achieves more coherence than they did precisely because of the philosophical angle, which is meant to serve as a complement, not an alternative, to theological and historical interpretations. Thus the book can be read as an introduction to the philosophy of Dionyius as it shows how the author makes original moves in introducing the Christian concepts of peace and creation as philosophical concepts in a Platonic framework.